Ägyptisches Buchwesen: koptische und griechische Interpunktion im Johannesevangelium - Sandmeier, Katharina D. (Arbeiten zur neutestamentlichen Textforschung, 2025)
"This volume is the first to provide a comprehensive study on punctuation in Coptic and Greek manuscripts from late ancient Egypt. It provides a nuanced exploration of how the reading aids functioned by looking at selected documents from the Gospel of John, identifying both similarities in the use of pauses in both languages as well as independent developments in Coptic punctuation"-- Provided by publisher